Parameters of the energy spectrum for holes in CuInSe₂ - Gorley, P.М.; Prokopenko, I.V.; Galochkinа, О.О.; Horley, P.P.; Vorobiev, Yu.V.; González-Hernández, J. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
This paper reports the coefficients Ca,b for the k-linear term in dispersion
relation E(k) for holes of the upper valence bands Г⁻₆ and Г⁺₇ in p-CuInSe₂ crystals. We
also obtained the tensor components for the carrier effective masses, in all three valence sub-bands of the model semiconductor. It was shown that the energy spectrum parameters for holes in CuInSe₂ allow successful explanation for the anisotropy of tensor
components describing the interband light absorption coefficient and the published data
for the temperature variation of the Hall coefficient, total Hall mobility and thermal
voltage within the temperature range 100 K ≤ T ≤ 350 K.